Association of the Nicotinic Receptor α7 Subunit Gene (CHRNA7) with Schizophrenia and Visual Backward Masking - Bakanidze, George; Roinishvili, Maya; Chkonia, Eka; Kitzrow, Werner; Richter, Sarina; Neumann, Konrad; Herzog, Michael; Brand, Andreas; Puls, Imke (Frontiers in Psychiatry, 2013)
The nicotinic system is involved in the pathophysiology of schizophrenia. However, very little is known about its genetic basis and how it relates to clinical symptoms and potentially pharmacological intervention. Here, we investigated five single nucleotide polymorphisms (SNPs) [rs3826029] [rs2337506] [rs982574] [rs904952] [rs2337980] of the cholinergic nicotinic receptor gene, alpha 7 subunit (CHRNA7) and their association to schizophrenia. We found an association with rs904952 (p=0.009) in a German sample of 224 schizophrenic patients and 224 healthy control subjects. The same trend was shown in an independent Georgian sample of 50 schizophrenic patients, 57 first order unaffected relatives, and 51 healthy controls. In addition, visual backward masking (VBM), a sensitive test for early visual information processing, was assessed in the Georgian sample. In line with prior studies, VBM performance deficits were much more pronounced in schizophrenic patients and their unaffected relatives compared to healthy controls (schizophrenic patients: 156 ms; unaffected relatives: 60 ms; healthy controls: 33 ms). VBM was strongly correlated with SNP rs904952 (H[2]=7.3, p=0.026). Our results further support the notion that changes in the nicotinic system are involved in schizophrenia and open the avenue for pharmacological intervention.